Music: an effective anxiolytic during caesarean section under spinal anaesthesia - Bansal, Gopal L.; Kaur, Harpreet; Shukla, Veena; Harsh, Harsh Kumar; Gupta, Anshul (International Journal of Research in Medical Sciences, 2019)
Background: Parturient undergoing repeat caesarean section (CS) under spinal anaesthesia usually experience anxiety due to unpleasant operative environment. Music therapy has been found to have positive psychological impact to relieve anxiety, improve patient satisfaction and provide stable haemodyanamics. Methods: Sixty patients without any co morbidity having history of previous CS, scheduled for another caesarean under spinal anaesthesia were included in the study. Patients were divided into two groups of 30 each. Group(M) patients were subjected to hearing music of their choice with the help of headphones after administration of spinal anaesthesia till the end of surgery. Group(N) patients were not made to listen to any music but headphones were applied. Haemodyanamic parameters including mean arterial pressure (MAP) and heart rate (HR), visual analogue score for anxiety (VASA) after administering spinal block and at the end of surgery, patient satisfaction score (PSS) and comparison of anxiety with previous CS were observed and recorded. Results: Both MAP and HR in Group M started falling after 10 minutes of spinal anaesthesia as compared to Group N and difference was significant (P <0.005), VASA 2 (2.2±1.8) in Group M was significantly lower than VASA 1 (5.4±1.7). PSS was also in favour of music group (Group M) and difference was highly significant as compared to group N (p=0.018). Patient’s anxiety as compared to anxiety with previous CS was lesser in Group M as compared to Group N(p=0.009). Conclusions: Music is a non-invasive tool to relieve anxiety during intraoperative period along with higher patient satisfaction and stable haemodyanamics.